Influence of corporate governance on cost of family open debt - Einsweiller, André Carlos; Moura, Geovanne Dias de; Kruger, Silvana Dalmutt (Contextus - Revista Contemporânea de Economia e Gestão, 2020)
The study verified the influence of corporate governance on the cost of debt of family owned companies. To this end, a descriptive, documentary and quantitative research was conducted on a sample of family companies that had data available for the period from 2012 to 2017. To measure the cost of debt, the ratio between financial expenses and the liability was identified. For corporate governance were used: a) adherence to the new market; b) have independent members on the board of directors; c) percentage of independent board members; d) majority of independent board members; e) non-duality as CEO and chairman. The results showed that corporate governance does not influence a reduction in the cost of debt in family businesses.